(untitled) (Politeja, 2020)
Kashubian Post-memory. Some Contemporary Examples The article contains analyses of several contemporary literary texts concerning the category of post-memory written in the background of the Kashubian culture. It mainly interprets prose works (Drewz, Bunda, Drzeżdżon) as well as the novel on which the film Kamerdyner was based. The analyses led to determining the phenomena defined by Sigmund Freud related to psychoanalysis and referring to the works by A. and J. Assmann, M. Hirsch and D. LaCapra. Thus Kashubian literature, written in Polish and Kashubian, shows post-memory mechanisms in the form of crowding out, transferring, repeating and overcoming the trauma of World War II.